2018
DOI: 10.25273/jipm.v7i1.2430
|View full text |Cite
|
Sign up to set email alerts
|

Developing Worksheet Based on Multiple Intelligences to Optimize the Creative Thinking Students

Abstract: The research and development of worksheet based on multiple intelligences aims to develop and describe the effectiveness of worksheet based on Multiple Intelligences to optimizing the ability of creative thinking students. The type of research used is research and development that refers to the theory of Borg &amp; Gall. The population of this research is the students of 5<sup>th</sup> grade of Primary School in Metro East. The sample of the study was 33 students of 5<sup>th</sup> g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…This result is in accordance with Ratnasari et al (2018) that learning with a multiple intelligence approach through quantum teaching models are more effective for improving scientific and scientific attitudes learning outcomes rather than learning by quantum teaching model. The results showed that the worksheet based on Multiple Intelligences effectively optimized students' creative thinking Luthfiana et al (2018) and Hutasuhut et al (2019) revealed his research that compound intelligencebased explanatory text teaching materials are feasible, easy and effective to use in learning in grade 11 vocational high schools. The present paper looks at internet as a suitable teaching tool which can accommodate diverse intelligences and learning preferences of multiple learners and can extend a great language teaching/learning experience.…”
Section: Resultsmentioning
confidence: 98%
“…This result is in accordance with Ratnasari et al (2018) that learning with a multiple intelligence approach through quantum teaching models are more effective for improving scientific and scientific attitudes learning outcomes rather than learning by quantum teaching model. The results showed that the worksheet based on Multiple Intelligences effectively optimized students' creative thinking Luthfiana et al (2018) and Hutasuhut et al (2019) revealed his research that compound intelligencebased explanatory text teaching materials are feasible, easy and effective to use in learning in grade 11 vocational high schools. The present paper looks at internet as a suitable teaching tool which can accommodate diverse intelligences and learning preferences of multiple learners and can extend a great language teaching/learning experience.…”
Section: Resultsmentioning
confidence: 98%
“…(3) Originality (Orisinil); ( 4) Elaboration (Rinci) [6,7,8]. Selama social distancing, pemerintah menganjurkan kegiatan pembelajaran dilakukan di rumah, baik dengan homevisit ataupun dengan daring [9] [10].…”
Section: Pendahuluanunclassified